Effects of carbohydrate, caffeine, and guarana on cognitive performance, perceived exertion, and shooting performance in high-level athletes - Pomportes, L.; Brisswalter, J.; Hays, A.; Davranche, K. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To investigate the effect of ingesting carbohydrate (CHO), caffeine (CAF), and a guarana complex (GUAc) during a running exercise on cognitive performance, rating of perceived exertion (RPE), and shooting performance in high-level modern pentathlon athletes. Methods: A total of 10 athletes completed 4 counterbalanced sessions within a 2-wk period, corresponding to ingestions of CHO (30 g), GUAc (300 mg), CAF (200 mg), or placebo. The exercise involved a 40-min run on a treadmill at a steady speed, previously determined as a "somewhat hard" exercise (RPE 13). Shooting and cognitive performance (Simon task) were assessed in 3 phases: before exercise and ingestion, before exercise and after half ingestion, and after exercise and full ingestion. Drinks were consumed 40 min (250 mL) and 5 min (125 mL) prior to exercise and after 20 min of running (125 mL). RPE was assessed at 10-min intervals during exercise. Results: There was an interaction between drink and exercise on mean reaction time (P = .01, 2p=.41 p2=.41) and a drink effect on RPE (P = .01, 2p=.15 p2=.15). CHO, CAF, and GUAc enhanced the speed of information processing after exercise (P = .003, P = .004, and P = .04, respectively), but only CAF and GUAc decreased RPE (P = .002 and P = .02, respectively). Conclusion: The results highlight a beneficial effect of nutritional supplements on information processing and RPE. This finding is particularly interesting as decision-making processes are crucial in the performance of many sports.